PEMBENTUKAN KARAKTER GEMAR MEMBACA DAN RASA INGIN TAHU SISWA MELALUI GERAKAN LITERASI SEKOLAH - Isa, Isa; Asrori, Asrori; Muharini, Rini (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to describe the formation of students' character ofÂ like to read and curiosity through the school literacy movement. The research was carried out using a descriptive method with the research subjects consisting of seven (7) teachers and staff and five (5) students at Al Azhar 21 Pontianak Islamic Elementary School. The data were collected through observation, interviews and documentation. The analysis technique are interactive model analysis which includes data reduction, data presentation, drawing conclusions and verification. The research results show that character formation corresponds to the three stages of the literacy movement, namely the habituation, development and learning stages. Forming a character who likes to read at Islamic Elementary School Al Azhar 21 Pontianak includes a mandatory reading program, library visits, providing a list of books or writings that students have read, carrying out reading book exchange activities, and learning using references. Meanwhile, the formation of a curious character includes providing communication media in the form of printed or electronic media for expression, facilitating school members to explore education, science, technology and culture, as well as creating an atmosphere that invites students' curiosity.